Role of Tunneling Nanotubes in Viral Infection, Neurodegenerative Disease, and Cancer - Tiwari, Vaibhav; Koganti, Raghuram; Russell, Greer; Sharma, Ananya; Shukla, Deepak (Frontiers in Immunology, 2021)
The network of tunneling nanotubes (TNTs) represents the filamentous (F)-actin rich tubular structure which is connected to the cytoplasm of the adjacent and or distant cells to mediate efficient cell-to-cell communication. They are long cytoplasmic bridges with an extraordinary ability to perform diverse array of function ranging from maintaining cellular physiology and cell survival to promoting immune surveillance. Ironically, TNTs are now widely documented to promote the spread of various pathogens including viruses either during early or late phase of their lifecycle. In addition, TNTs have also been associated with multiple pathologies in a complex multicellular environment. While the recent work from multiple laboratories has elucidated the role of TNTs in cellular communication and maintenance of homeostasis, this review focuses on their exploitation by the diverse group of viruses such as retroviruses, herpesviruses, influenza A, human metapneumovirus and SARS CoV-2 to promote viral entry, virus trafficking and cell-to-cell spread. The later process may aggravate disease severity and the associated complications due to widespread dissemination of the viruses to multiple organ system as observed in current coronavirus disease 2019 (COVID-19) patients. In addition, the TNT-mediated intracellular spread can be protective to the viruses from the circulating immune surveillance and possible neutralization activity present in the extracellular matrix. This review further highlights the relevance of TNTs in ocular and cardiac tissues including neurodegenerative diseases, chemotherapeutic resistance, and cancer pathogenesis. Taken together, we suggest that effective therapies should consider precise targeting of TNTs in several diseases including virus infections.